Predicting Cognitive Decline across Four Decades in Mutation Carriers and Non-carriers in Autosomal-Dominant Alzheimer's Disease. (12th January 2017) - Almkvist, Ove; Rodriguez-Vieitez, Elena; Thordardottir, Steinunn; Amberla, Kaarina; Axelman, Karin; Basun, Hans; Kinhult-Ståhlbom, Anne; Lilius, Lena; Remes, Anne; Wahlund, Lars-Olof; Viitanen, Matti; Lannfelt, Lars; et al.
Abstract: Objectives: The aim of this study was to investigate cognitive performance including preclinical and clinical disease course in carriers and non-carriers of autosomal-dominant Alzheimer's disease (adAD) in relation to multiple predictors, that is, linear and non-linear estimates of years to expected clinical onset of disease, years of education and age.Methods: Participants from five families with early-onset autosomal-dominant mutations (Swedish and Arctic APP, PSEN1 M146V, H163Y, and I143T) included 35 carriers (28 without dementia and 7 with) and 44 non-carriers. All participants underwent a comprehensive clinical evaluation, including neuropsychological assessment at the Memory Clinic, Karolinska University Hospital at Huddinge, Stockholm, Sweden. The time span of disease course covered four decades of the preclinical and clinical stages of dementia. Neuropsychological tests were used to assess premorbid and current global cognition, verbal and visuospatial functions, short-term and episodic memory, attention, and executive function.Results: In carriers, the time-related curvilinear trajectory of cognitive function across disease stages was best fitted to a formulae with three predictors: years to expected clinical onset (linear and curvilinear components), and years of education. In non-carriers, the change was minimal and best predicted by two predictors: education and age. The trajectories for carriers and non-carriers began to diverge approximately 10 years before the expected clinical onset in episodic memory, executive function, and visuospatial function.Conclusions: The curvilinear trajectory of cognitive functions across disease stages was mimicked by three predictors in carriers. In episodic memory, executive and visuospatial functions, the point of diverging trajectories occurred approximately 10 years ahead of the clinical onset compared to non-carriers. ( JINS, 2017, 23, 195–203)